A History of Hmong Men: Peb Leej Txiv Lub Neej (Our Father's Lives) - Her, Khong Meng (My University, 2013)
Through the story of Cher Her, a Hmong man, this paper will discuss the lives and experiences of Hmong men during the evacuation of Long Cheng in 1975, the journey to the refugee camps, and leaving Thailand for resettlement in America. This narrative addresses how these men escaped persecution from communist forces, and led their families to refugee camps in Thailand. The flight presented many challenges: coping with new laws, their masculinity and pride taken away from them. It explores how the lives of Hmong men were affected by leaving Thailand, an place similar to their homeland, and entering a new world where social economics and culture shock has "flipped them upside down," feeling like they now reside at the bottom of the family structure.
Keywords: Her, Cher; Men, Hmong--Psychology; Men, Hmong--Personal narratives; Refugees--Thailand--Personal narratives; Refugees--United States--Cultural assimilation; Hmong Americans--Cultural assimilation